The Dynamics of Heritagization in Urban Regeneration: East-West Dichotomy - Hanif, Saad; Riza, Müge (Alanya Üniversitesi, 2025)
Heritagization —the process of assigning heritage value to places, objects, or traditions— has become increasingly entwined with urban regeneration initiatives. However, its theoretical grounding remains underdeveloped, particularly regarding its diverse expressions across Eastern and Western contexts. This study examines the dynamics of heritagization as both a cultural and socio-political process within urban regeneration, drawing on the framework of Critical Heritage Studies. Using a descriptive qualitative methodology and global case-based literature review, the research dissects how heritage is strategically reinterpreted to fulfil contemporary socio-economic and political goals. Findings reveal a clear East–West dichotomy: while Western practices often commodify heritage for branding and tourism, Eastern cases reflect heritage as a tool for identity reconstruction, postcolonial resilience, and state-led regeneration. The study argues that heritagization should be understood not as a Western-centric imposition, but as a globally variable process shaped by local agency, historical context, and development agendas. To support this claim, the paper presents comparative process diagrams delineating regional differences. Ultimately, this research contributes to a more nuanced, decolonised understanding of heritagization in the built environment.